Religious Pluralism in Indonesia's Multicultural Society - Engkos Koswara; R.F. Bhanu Viktorahadi (Kongregasi Hati Kudus Yesus (RSCJ) Indonesia, 2022)
Indonesia is a multi-ethnic, multicultural and multi-religious nation where religions are developed and adhered to and are inseparable from a plural society. Sociologically, religious pluralism is a fact that we are different, diverse, and plural in terms of religion. The existence of these religions is a particular challenge that each religious believer must face because pluralism is already around us, and not no one can refuse it again. In such conditions, tolerance and interfaith dialogue of religious adherents are the primary capital in maintaining the integrity of plural and multicultural religious communities.